Gene regulation in hematopoiesis: new lessons from thalassemia. - Higgs, D (2004)
Over the past fifty years, many advances in our understanding of the general principles controlling gene expression during hematopoiesis have come from studying the synthesis of hemoglobin. Discovering how the alpha and beta globin genes are normally regulated and documenting the effects of inherited mutations which cause thalassemia have played a major role in establishing our current understanding of how genes are switched on or off in hematopoietic cells. Previously, nearly all mutations causing thalassemia have been found in or around the globin loci, but rare inherited and acquired trans-acting mutations are being found with increasing frequency. Such mutations have demonstrated new mechanisms underlying human genetic disease. Furthermore, they are revealing new pathways in the regulation of globin gene expression which, in turn, may eventually open up new avenues for improving the management of patients with common types of thalassemia.